ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI USAHATANI PADI SAWAH di DESA AMPERA KECAMATAN PALOLO KABUPATEN SIGI - Moh. Rianto; Saharia Kassa; Husnul Khatima (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
As the main food crop for the Indonesian population, rice. Rice is a staple food for the people of Indonesia, and it plays a crucial role in ensuring food security in the country. The study aimed to determine the magnitude of the influence of the different factors such as land area, seeds, fertilizers, pesticides and labor on the production of lowland rice farming in Ampera Village, Palolo District, Sigi Regency. The number of 35 respondents was calculated using the Slovin formula. The study used multiple regression analysis with the Cobb-Douglas production function model to analyze the data. it was found that the variables of land area, seeds, fertilizer, pesticides, and labor simultaneously had a significant effect on the production of lowland rice farming. This means that increasing the land area, using quality seeds, applying appropriate fertilizers and pesticides, and employing more labor can all contribute to higher rice production.